Looking into waqf (religious endowment) potentials for stratified properties maintenance and management in Malaysia - Mohamad, Nor Asiah; Sufian, Azlinor (Universiti Tun Abdul Razak Sdn Bhd in collaboration with International Centre for Waqf Research (ICWR) of International Islamic University Malaysia (IIUM), Malaysia, 2017)
Vertical living is common in Malaysia as well as other parts of the world. High cost of land and lack of strategic location for housing estates has influenced the developers to opt for vertical development. Stratified properties are divided into two; self-owned unit and common property which are commonly owned and managed by all owners of the strata scheme. The challenge, most of the times, involves the maintenance of the common areas which requires substantial budget and professionalism, skills in developing social and human relationship and lastly, the continualincrease of cost ofmanagement of the properties which requires visionary and skillful strata managers. Above all, financial standing and professionalism is vital. Using doctrinal analysis of the primary and secondary data, the findings conclude that the concept of Waqfor endowment as catalyst for the third sector economy can play a role as a potential vehicle to raise funds to maintain and manage common properties in strata scheme. While religious reward may motivate the Muslim owners or tenants to contribute to waqf fund, other benefits such as financial security, sustainability, accountability and transparency would invite contribution and build trust from the Muslim and non-Muslim. With adequate education initiatives and effective marketing of waqf products, waqf concept shall provide sustainable source of fund to cater short term and long term maintenance plan for strata scheme.